Ответ:
Объяснение:
!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Объяснение:Используем формулу косинуса суммы двух углов
Cos(α+β)= Cosα·Cosβ - Sinα·Sinβ,
тогда Cos34°·Cos26° - Sin34·°Sin26° = Сos(34°+26°)=Сos60°=1/2
Ответ: А 1/2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Ответ:
Объяснение:Используем формулу косинуса суммы двух углов
Cos(α+β)= Cosα·Cosβ - Sinα·Sinβ,
тогда Cos34°·Cos26° - Sin34·°Sin26° = Сos(34°+26°)=Сos60°=1/2
Ответ: А 1/2